National guideline for the field triage of injured patients: Recommendations of the National Expert Panel on Field Triage, 2021. Issue 2 (27th August 2022) - Newgard, Craig D.; Fischer, Peter E.; Gestring, Mark; Michaels, Holly N.; Jurkovich, Gregory J.; Lerner, E. Brooke; Fallat, Mary E.; Delbridge, Theodore R.; Brown, Joshua B.; Bulger, Eileen M.
Abstract : This work details the process of developing the updated field triage guideline, the supporting evidence, and the final version of the 2021 National Guideline for the Field Triage of Injured Patients. Abstract :